Interleaved 23Na/1H MRI of the human heart at 7 T using a combined 23Na/1H coil setup and 1H parallel transmission - Ruck, Laurent; Egger, Nico; Wilferth, Tobias; Schirmer, Judith; Gast, Lena; Nagelstraßer, Sophia; Wildenberg, Saskia; Bitz, Andreas; Lanz, Titus; Platt, Tanja; Konstandin, Simon; Kopp, Christoph; et al. (Magnetic Resonance in Medicine, 2025)
Purpose: To evaluate the feasibility of interleaved 23Na/1H cardiac MRI at 7 T using 1H parallel transmission (pTx) pulses. Methods: A combined setup consisting of a 23Na volume coil and two 1H transceiver arrays was employed and the transmit and receive characteristics were compared in vitro with those of the uncombined radiofrequency coils. Furthermore, the implemented interleaved 23Na/1H pTx sequence was validated in phantom measurements and applied to four healthy subjects. For the latter, three customized 1H excitation pulses (universal and individual phase shims (UPS/IPS) and individual 4kT pulses (4kT)) were employed in the interleaved 23Na/1H pTx sequence and compared with the vendor-provided default cardiac phase shim (DPS). Results: Combining both coils resulted in a reduction of the mean 23Na transmit field (B1+) efficiency and 23Na signal-to-noise ratio by 18.9% and 15.4% for the combined setup, whereas the 1H B1+ efficiency was less influenced (−4.7%). Compared with single-nuclear acquisitions, interleaved dual-nuclear 23Na/1H MRI showed negligible influence on 23Na and 1H image quality. For all three customized 1H pTx pulses the B1+ homogeneity was improved (coefficients of variation: CVUPS = 0.30, CVIPS = 0.23, CV4kT = 0.15) and no 1H signal dropouts occurred compared with the vendor-provided default phase shim (CVDPS = 0.37). Conclusion: The incorporation of customized 1H pTx pulses in an interleaved 23Na/1H sequence scheme was successfully demonstrated at 7 T and improvements of the 1H B1+ homogeneity within the heart were shown. Combining interleaved 23Na/1H MRI with 1H pTx is an important tool to enable robust quantification of myocardial tissue sodium concentrations at 7 T within clinically acceptable acquisition times.
CRIS-Team Scopus Importer:2025-04-01
Keywords: 7 Tesla; cardiac sodium (; interleaved acquisition; parallel transmission (pTx)